Vaporwave's visual language legacy: representetion in the late stages of capitalism (DAPesquisa, 2021)
The article is concerned with the Vaporwave movement’s visuality, grounding in Hall (1997) the system of language - its codes and the construction of meanings, conformed by signs. In this sense, the cover of the album “Floral Shoppe” (2011) is analyzed, identifying the visual elements and the context of their political messages, later discussed in the face of appropriation by large corporations, even if they are ideologically opposed.
Keywords: Graphic arts - Vaporwave (Music); Memes; Visual communication in art; Language and the Internet